Essentials from the 2015 European AIDS Clinical Society (EACS) guidelines for the treatment of adult HIV‐positive persons. Issue 2 (8th November 2015) - Ryom, L; Boesecke, C; Gisler, V; Manzardo, C; Rockstroh, JK; Puoti, M; Furrer, H; Miro, JM; Gatell, JM; Pozniak, A; Behrens, G; Battegay, M; et al.
Abstract : Background: The European AIDS Clinical Society (EACS) guidelines are intended for all clinicians involved in the care of HIV‐positive persons, and are available in print, online, and as a free App for download for iPhone and Android. Guideline highlights: The 2015 version of the EACS guidelines contains major revisions in all sections; antiretroviral treatment (ART), comorbidities, coinfections and opportunistic diseases. Among the key revisions is the recommendation of ART for all HIV‐positive persons, irrespectively of CD4 count, based on the Strategic Timing of AntiRetroviral Treatment (START) study results. The recommendations for the preferred and the alternative ART options have also been revised, and a new section on the use of pre‐exposure prophylaxis (PrEP) has been added. A number of new antiretroviral drugs/drug combinations have been added to the updated tables on drug−drug interactions, adverse drug effects, dose adjustment for renal/liver insufficiency and for ART administration in persons with swallowing difficulties. The revisions of the coinfection section reflect the major advances in anti‐hepatitis C virus (HCV) treatment with direct‐acting antivirals with earlier start of treatment in individuals at increased risk of liver disease progression, and a phasing out of interferon‐containing treatment regimens. The section on opportunistic diseases has been restructured according to individual pathogens/diseases and a new overview table has been added on CD4 count thresholds for different primary prophylaxes. Conclusions: The diagnosis and management of HIV infection and related coinfections, opportunistic diseases and comorbidities continue to require a multidisciplinary effort for which the 2015 version of the EACS guidelines provides an easily accessable and updated overview.